2017
DOI: 10.7150/ijbs.21457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and in vitro analysis of Osteopontin as a prognostic indicator and unveil its potential downstream targets in bladder cancer

Abstract: Osteopontin (OPN) plays an important role in cancer progression, however its prognostic significance and its downstream factors are largely elusive. In this study, we have shown that expression of OPN was significantly higher in bladder cancer specimens with higher T-stage or tumor grades. In addition, a high level of OPN was significantly associated with poorer survival in two independent bladder cancer patient cohorts totaling 389 bladder cancer patients with available survival data. We further identified Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
(83 reference statements)
2
27
0
Order By: Relevance
“…It has been well known that OPN overexpression has enhanced tumour behaviour, but the potential co‐regulation genes involved in this complex process have not been well identified. In our previous work, we have shown that the expression of OPN and MMP9 were positively correlated in human bladder cancer specimens and bladder cancer cell lines . In the present study, we found that overexpression of OPN up‐regulated MMP9 while OPN and MMP9 expression levels were positively correlated in two independent colon cancer datasets.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It has been well known that OPN overexpression has enhanced tumour behaviour, but the potential co‐regulation genes involved in this complex process have not been well identified. In our previous work, we have shown that the expression of OPN and MMP9 were positively correlated in human bladder cancer specimens and bladder cancer cell lines . In the present study, we found that overexpression of OPN up‐regulated MMP9 while OPN and MMP9 expression levels were positively correlated in two independent colon cancer datasets.…”
Section: Discussionsupporting
confidence: 68%
“…The p3XFLAG‐CMV‐7.1 (Sigma, E7533) was ligated to the N‐terminal of OPN‐c gene of pcDNA3‐OPN‐V5, which was a gift from Steven Johnson (Addgene plasmid # 11617) . Then it was inserted into pBABE‐puro which was a gift from Hartmut Land, Jay Morgenstern and Bob Weinberg (Addgene plasmid # 1764) .…”
Section: Methodsmentioning
confidence: 99%
“…Regarding BCa, immunohistochemical staining of OPN demonstrated significant correlation with tumor stage (27). More recently, Wong and colleagues showed that OPN expression correlates with disease stage and grading and that higher OPN expression led to decreased survival in multiple patient cohorts (26). Of note, we could not see the same in our TCGA data set when applying median expression for overall and diseasefree survival (Supplementary Figure 9).…”
Section: Nrp2 Positively Regulates Osteopontin Expressionmentioning
confidence: 69%
“…However, only one gene transcript was regulated in a similar manner to NRP2 knockout in RT112 as well as NRP2 knockdown in J82 ( Figure 6C). The SPP1 gene (Osteopontin, OPN) was previously reported to be induced by VEGF (25) and to be associated with decreased survival, disease stage, and grading in BCa (26,27). Previous findings support the role of SPP1 as one of the key EMT regulators (28).…”
Section: Knockout Of Nrp2 Alters Gene Expression Of Emt Regulatorsmentioning
confidence: 75%
“…Fouad et al [15] revealed that MMP-9 was significantly up-regulated in both blood and urine of BCa patients and was of great discriminatory ability in the diagnosis of BCa. Wong et al [16] also demonstrated that MMP9 was a potential therapeutic target and prognostic biomarker that contribute to the progression of BCa. There have been several studies confirming the role of IGF-1, an anti-apoptotic peptide, in the progression of BCa.…”
Section: Discussionmentioning
confidence: 98%